Melinopini biodiversity and medicinal uses of the honey from El Oro province in Ecuador - Vit, Patricia; Vargas, Oliverlo; López, Triny; Maza, Favián (My University, 2015)
Ecuadorian stingless bees (Apidae, Meliponini) have ethnomedicinal interest because their products are used in healing. Diversa remedies consist on pot-honey alone ar mixed with infusions. This set of medicinal uses were informed in El Oro province by Ecuadorian stingless bee keepers known as meliponicultors in Latín Ameríca: Bruises, tumors, ocular cataracts, pterygium, inflammation, infections, varicose veins, cleaning blood after childbirth, kidney diseases, tumor, wound healing, and soothing balm befare sleeping. Scaptotrigona ederi named canana is the most frequent bee in the visited cantons Las Lajas, Balsas, Piñas, and Zaruma. Other important stingless bees are Melipona indecisa cananambo, Melipona mimetica bermejo, Nannotrigona cf. perilampoides pitón, and Paratrigona aff. eutaeniata pirunga. A bioprospective research will follow to value this ancient tradition and the
Keywords: TUMOR; ANTIOXIDANT; EMIRATES JOUMAL OF FOOD AND AGRICULTURE